Urban securitization in the historic district of Valencia: actors, dispositives and narratives - Fioravanti, Hernán (Revista de Antropología Social, 2022)
This article presents an ethnographic analysis of the urban securitization processes that are taking place in a neighbourhood located in the historic district of Valencia. We trace a political economy of urban securitization at the local scale, looking at the role played by a plurality of actors, including neighbours, urban movements, police forces, and local institutions. The analysis focuses on a multiplicity of security dispositives and tactics, from preventive architectures and punitive urbanism to the policialization of neighbourhood sociabilities and the implementation of civility ordinances, all the way to private surveillance systems. We also study the discourses and collective imaginaries that underlie this dynamic, reflecting on how urban marginality and ​​neighbourhood belonging are regarded. We conclude by pointing out the connections between urban securitization and the processes of population displacement